Let's solve the equation step by step:
4(2 - 3x) = x - 2(2x + 1)
First, distribute the 4 on the left side and the -2 on the right side:
8 - 12x = x - 4x - 2
Combine like terms on both sides:
8 - 12x = -3x - 2
Next, move all the terms involving x to one side:
-12x + 3x = -2 - 8
Simplify:
-9x = -10
Now, divide both sides by -9 to solve for x:
x = (-10) / (-9)
Simplifying further:
x = 10/9
Therefore, the equation has only one solution: x = 10/9.
how many solutions does 4 (2 - 3x) = x - 2 (2x + 1) have
1 answer